The anatomy of Lebanon’s postwar integral state: the political economy of cartels and consent - Bassel F. Salloukh (17704392) (2025)
This essay stretches Antonio Gramsci’s core concept of the integral state to explain an enigma in contemporary Lebanon: why the massive collapse after the October 2019 protests failed to generate commensurate political, ideological, and organizational responses. It retheorizes the post-civil war state in Lebanon as a different kind of integral state, one that reflects an alternative process of state formation and historical trajectory in the Global South producing different state forms, class fractions, and social formations than those in Europe. In this case, private elite interests expressing different class fractions operate not by defining the ethical content of the state in civil society, nor by organizing consent on the cultural front of civil society, but overlap directly with state structures. Stretching Gramsci’s conceptual toolkit dissolves the differences between the state and society, and captures analytically how the postwar political economic elite representing an alliance of class fractions placed the state’s fiscal and monetary policies at the service of capital accumulation, but also to integrate substantial social constituencies into the postwar order along strictly sectarian clientelist incentives. This disaggregated cross-sectarian class interests and provided the material conditions to secure a level of sectarian ideological consent that precluded the emergence of viable political alternatives in the postwar era. The operations of the postwar integral state also truncated the terrain of civil society on which alternative organizational formations could organize in the long war of position to subvert the ideological hold of the sectarian system. The anatomy of this postwar integral state is examined as expressed in the political economy of cartels. Other Information Published in: Interventions License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/1369801x.2025.2504922